Escape the cape, from existing to evolving : amplifying voices of black and brown women in the mental health profession - Wilson, Tasha M. (Research, theory, and practice within academic affairs., 2025)
Escape the Cape, From Existing to Evolving: Amplifying Voices of Black and Brown Women in the Mental Health Profession examines the narratives of Black and Brown women all over the world who adherently take on the Superwoman Persona. The imaginative armor of a cape contributes to the normalcy of trying to "do it all" for others while neglecting the self. The book amplifies the voices of Black and Brown women in the mental health and academia professions who needed a healthy outlet to shed light on their experiences. This book stems from an asset-based approach where chapter authors highlight the ebbs and flows they experienced in the workplace due to having melanated skin and/or identifying as Black and Brown. So many Black and Brown women have suffered in silence because of exploitive workplace politics and practices and haven't felt safe, valued, or heard; the "need" of Black and Brown women became greater than their humanity. Escape the Cape, From Existing to Evolving is a call to action. It contributes to elevating scholarly conversations for employers who are seeking strategies in promoting equity in the workplace.